Thébault’s Pencil of Circles in an Isotropic Plane - Volenec, Vladimir; Kolar-Begović, Zdenka; Kolar-Šuper, RužicA (Sarajevo Journal of Mathematics, 2024)
In the Euclidean plane Griffiths's and Thébault's pencil of the circles are generally different. In this paper it is shown that in an isotropic plane the pencils of circles, corresponding to the Griffiths's and Thébault's pencil of circles in the Euclidean plane, coincide. 2000 Mathematics Subject Classification. 51N25